The impact of the gradual activities strategy on developing the teaching skills of students at an institute with fine arts subjects, viewing and applying (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of the gradual activities strategy on developing the teaching skills of students of the Institute of Fine Arts in the subject of viewing and application( In the first chapter, the researcher addressed the importance of the research, the limits of the research, research terms and their definitions, while the second chapter dealt with the theoretical framework, which includes the first axis of the theoretical framework and includes the first section (gradual activities strategy), the second section (constructivist theory), the third section (teaching skills), and the fourth section ( Observation and application) The second axis also included (studies that dealt with graded activities, teaching skills, observation and application, balancing between previous studies, aspects of benefiting from previous studies( In terms of procedures in the third chapter, the researcher adopted the experimental method with partial control for the two groups (experimental and control) with the application of a pre- and post-test. The research sample consisted of (52) fifth-grade students - Institute of Fine Arts / in Baghdad Governorate / Al-Karkh - Al-Mansour area. Equivalence of the two research groups (experimental and control) in intelligence and age in months, controlling for variables The study obtained its results with superiority to the experimental group that studied according to the strategy of cognitively and skillfully graded activities prepared by the researcher, through the fourth chapter with the subject of observation and application, and then the conclusions, recommendations, and sources.